Birmingham Intervention Tent Technique (BITT): A Technical Note - Rajakulasingam, R.; Kho, J.; Almeer, G.; Azzopardi, C.; James, S. L.; Botchu, R. (Indian Journal of Radiology and Imaging, 2021)
Objective We describe a novel and safe CT biopsy technique that we have termed the “Birmingham intervention tent technique (BITT).” This technique is ideal for biopsying osseous lesions where a direct approach is not possible due to difficult positioning.Methods The BITT uses a plastic surgical forceps clamp attached at an angle to the biopsy needle, creating a tent shape. The finger rings of the forceps is stabilized on the table.Results In our institution, we have already used the BITT successfully in over 10 cases.Conclusion The BITT is an inexpensive and reproducible technique.
Keywords: intervention; tent; technique